2022
DOI: 10.1371/journal.pcbi.1009504
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent thresholds of dexamethasone destabilize CAR T-cell treatment efficacy

Abstract: Chimeric antigen receptor (CAR) T-cell therapy is potentially an effective targeted immunotherapy for glioblastoma, yet there is presently little known about the efficacy of CAR T-cell treatment when combined with the widely used anti-inflammatory and immunosuppressant glucocorticoid, dexamethasone. Here we present a mathematical model-based analysis of three patient-derived glioblastoma cell lines treated in vitro with CAR T-cells and dexamethasone. Advanced in vitro experimental cell killing assay technologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…We compared the data first model discovery methodology of SINDy against the CARRGO model, a traditional model first approach originally used to analyze and interpret the CAR T-cell killing dynamics (18, 25). The CARRGO model is defined as, where we have expressed the parameter variables of the CARRGO model in terms of those used in the SINDy model for ease of comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We compared the data first model discovery methodology of SINDy against the CARRGO model, a traditional model first approach originally used to analyze and interpret the CAR T-cell killing dynamics (18, 25). The CARRGO model is defined as, where we have expressed the parameter variables of the CARRGO model in terms of those used in the SINDy model for ease of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The data analyzed in this study come from previously conducted experiments whose procedures are described in Sahoo et al (18) and Brummer et al (25), and summarized in Figure 1. The primary brain tumor cell line studied (PBT128) was selected for its endogenous high and relatively uniform expression of IL13R α 2 antigen (89.11% IL13R α 2+) (25). This cell line was derived from glioblastoma tumor resection tissue as described in (44, 45).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, low-dose dexamethasone did not reduce CAR T cell antitumor effects in orthotopic xenograft GBM models ( 63 ). By introducing a mathematical model, it was suggested that a critical threshold of CAR T cell death concerning the proliferation rate could guide the dose and timing of CAR T cell delivery in patients administered dexamethasone ( 64 ). Future clinical studies are required to determine the effects of dexamethasone on CAR T therapy.…”
Section: Additional Chemical and External Treatmentsmentioning
confidence: 99%